Energy harvesting techniques for routing issues in wireless sensor networks. (2019) - Ahmed, Sheeraz; Khan, Muhammad Ayub; Ishtiaq, Atif; Khan, Zahoor Ali; Ali, Malik Taimur
Recent years have seen remarkable advancement in the field of Energy Harvesting Wireless Sensor Networks (EH-WSNs). The popularity of energy harvesting has grown owing to its capability of prolonging the network lifetime. The devices utilising energy harvesting are affected by inefficiencies including energy leakage, and battery degradation or storage losses. Many different protocols are being developed in recent years in this domain. These protocols can be categorised in a variety of ways with respect to their mechanisms and functionalities they follow; hence, it becomes important to understand their working principle. In this research, we have selected some recent routing protocols in the field of EH-WSNs and present a comparative analysis in accordance to their categories in which they lie. A detailed analysis of their key advantages and flaws is also identified in this research.